A stakeholder map for climate change adaptation in Mali's agriculture sector - Aberman, Noora-Lisa; Haglund, Eric; Koné, Daouda (International Food Policy Research Institute, 2011)
This report presents the results of a stakeholder analysis, which had the following objectives: - to identify potential partners in the research process, - to find out which organizations could make use of the research findings in their activities, and - to derive implications for the communication and outreach strategy of the research project. In addition to a review of documents and individual interviews, a stakeholder analysis workshop was conducted in Ethiopia on August 9, 2011. A participatory mapping tool referred to as Net-Map was used to conduct the stakeholder analysis. The results of the stakeholder analysis are expected to be useful not only for the “Enhancing Assets” project, but also for other organizations and projects that work in this policy field.